Quantitative adverse outcome pathway modeling for cigarette-smoke-induced airway mucus hypersecretion. Part 1: adverse-outcome-pathway-based in vitro assessment with repeated exposure to whole cigarette smoke - Ichikawa, Sakuya; Muratani, Shugo; Sano, Keigo; Erami, Kazuo; Mori, Akina; Matsumoto, Risa; Ito, Shigeaki (Frontiers in Toxicology, 2025)
Adverse outcome pathway (AOP)-based chemical risk assessment is a promising tool for regulatory decision-making and is typically used in toxicological assessments. However, it also holds potential for pharmacological and disease-related evaluations. The present study focuses on an AOP for decreased lung function. Lung function is normally robustly maintained by homeostatic capacity, but repeated and chronic stimulation can disrupt this capacity, leading to impaired lung function and mucus hypersecretion. We developed an AOP-based in vitro method to test the disease-related states that can be reproduced by exposing three-dimensionally cultured human bronchial epithelial cells (3D-HBECs) to whole cigarette smoke (WCS). Over a duration of 2 weeks, we repeatedly exposed 3D-HBECs from six different donors to WCS six times to observe both acute phase responses (oxidative stress, epidermal growth factor receptor activation, and SP1 activation) and chronic phase responses (intracellular mucus production, goblet cell metaplasia/hyperplasia, and mucus hypersecretion) along the AOP. Our results demonstrate that although the repeated exposure to WCS induced biological responses along the AOP in all donors, there were interdonor differences, particularly in the timing and amplitudes of the chronic phase responses. All smokers do not exhibit phenotypic changes with the same smoking duration, so this variability likely reflects individual differences. We anticipate that our AOP-based assessment method combined with computational quantitative AOP modeling (discussed in Part 2) will become a valuable tool for assessing the disease risk of airborne materials and inhalable products.